Brazilian National Exam on Students' Performance (Enade) in Dentistry: Quantitative and Qualitative Analysis of the 2016 National Exam - Moimaz, Suzely Adas Saliba [UNESP]; Amaral, Marcelo Augusto [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Tânia Adas [UNESP] (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2018)
Objective: To analyze the Brazilian National Exam on Students' Performance (Enade) on Dentistry, with regard to its specific contents, and discusses the subareas dealt with on Community Health. Material and Methods: A documentary and descriptive research on the 2016 Enade was undertaken. The textual contents of the questions were processed by IRAMUTEQ and analyzed by lexicographic techniques Descending Hierarchical Classification and Word Cloud. Results: Community Health (12 questions), with 40.0% of the exam's contents, was the held with the greatest amount of questions. Subareas 'Management and Public Health Policies' and 'Administrative and Operational Management' featured five questions each (16.7%). Quantitative and qualitative analysis of the textual corpus detected 2,601 occurrences of words, mean 86.7 words per question. There were 858 different words, out of which 547 (average over 3.1 occurrences per question), which were included by the software within the Descending Hierarchical Classification. Five classes were provided: Humanization, Management, Strategy Family Health, Health Policy and Integrated Clinical Practice. The latter predominated (25.4%), characterized by the terms: anamnesis (chi(2)= 16.1), lesion (chi(2)= 12.6) and exam (chi(2)= 12.1). Conclusion: Community Health was predominant in the 2016 Enade and showed the importance of the theme within the professional profile of the future dentist. Contents on Health Policy, Strategy Family Health, Humanization and Management also proved to be relevant.
Keywords: Educational Measurement; Education, Graduate; Teaching; Dentistry